Mechanisms For Poverty Alleviation In Society - Danabayev Khurshid Napasovich (Zien Journals, 2024)
This article focuses on the issue of combating poverty and its prevention. In this regard, views on corruption as a negative social phenomenon and its objective factors are presented.
Keywords: Poverty; individual; society